2018
DOI: 10.1093/ibd/izx035
|View full text |Cite
|
Sign up to set email alerts
|

Safety, Clinical Response, and Microbiome Findings Following Fecal Microbiota Transplant in Children With Inflammatory Bowel Disease

Abstract: A single FMT is relatively safe and can result in a short-term response in young patients with active IBD. Responders possessed increased Fusobacterium prior to FMT and demonstrated more significant microbiome changes compared with nonresponders after FMT. Microbiome characteristics may help in predicting response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
135
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(144 citation statements)
references
References 43 publications
7
135
0
2
Order By: Relevance
“…The clinical response rates of 86.7% and 66.7% (at 1 month and 6 months, respectively), 77.8% (7 of 9 patients), 57.9% (11 of 19 patients), 71% and 42% (at 1 month and 6 months, respectively) have been reported separately in four clinical trials (Cui et al 2015a; Goyal et al 2018; Suskind et al 2015; Vaughn et al 2016). However, how to maintain the long-term response of remodeling microbiota in CD based on FMT is another critical question.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The clinical response rates of 86.7% and 66.7% (at 1 month and 6 months, respectively), 77.8% (7 of 9 patients), 57.9% (11 of 19 patients), 71% and 42% (at 1 month and 6 months, respectively) have been reported separately in four clinical trials (Cui et al 2015a; Goyal et al 2018; Suskind et al 2015; Vaughn et al 2016). However, how to maintain the long-term response of remodeling microbiota in CD based on FMT is another critical question.…”
Section: Discussionmentioning
confidence: 98%
“…Several pilot studies have shown that FMT could effectively induce clinical response in patients with active CD (Colman and Rubin 2014; Cui et al 2015a; Goyal et al 2018; Suskind et al 2015; Vaughn et al 2016). The clinical response rates of 86.7% and 66.7% (at 1 month and 6 months, respectively), 77.8% (7 of 9 patients), 57.9% (11 of 19 patients), 71% and 42% (at 1 month and 6 months, respectively) have been reported separately in four clinical trials (Cui et al 2015a; Goyal et al 2018; Suskind et al 2015; Vaughn et al 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike the effect of microflora transplantation on recurrent CDI, the results of many studies on FMT in UC are heterogeneous [123][124][125][126][127][128][129][130][131][132] owing to the lack of a standardized process ( Table 2). 9 One study suggests that the microbial imbalance of the CDI + UC recipients is similar to that of CDI-only recipients 140 Thus, the efficacy for FMT treatment in UC is probably attributed to the occurrence of bacterial dysregulation similar to that seen in CDI.…”
Section: Effectiveness Of Fmtmentioning
confidence: 99%
“…Ananthakrishnan et al [184] have studied the response to antiintegrin biologic therapy in association with the microbiome and have concluded that microbial function and diversity in early stages of therapy might be able to predict its efficacy. Finally, many studies have focused on fecal microbiota transplantation (FMT) [185][186][187][188][189] as a potential therapeutic action versus IBD, but also as a possible irritant [190,191].…”
Section: Microbiome In Ibd: the Meta-paradigmmentioning
confidence: 99%